Efficacy of Once Daily Darunavir/Ritonavir in PI-Naïve, NNRTI-Experienced Patients in the ODIN Trial. (18th August 2015) - Geretti, Anna Maria; Moeketsi, Mathe; Demasi, Ralph; van Delft, Yvon; Mohammed, Perry
Abstract : Background . An exploratory subanalysis of the ODIN trial was performed to evaluate the efficacy of darunavir/ritonavir (DRV/r) 800/100 mg OD versus 600/100 mg BID in patients who were NNRTI-experienced but PI-naïve. Methods . ODIN was a phase III, 48-week study comparing DRV/r OD versus BID in 590 treatment-experienced patients with no DRV resistance-associated mutations (RAMs) at screening. Patients received DRV/r 800/100 mg OD or DRV/r 600/100 mg BID plus ≥2 NRTIs. Of the 590 patients randomized, 272 (46%) were NNRTI-experienced but PI-naïve. Results . Overall, 272 patients received DRV/r OD n = 135 or BID n = 137 plus ≥2 optimised NRTIs. The mean age was 39 years; 35% were female; 27% were Black, 24% Caucasian, 26% Oriental/Asian, and 23% other races; 17% were recruited in South Africa; and 48% had non-B HIV-1 subtypes. Mean baseline plasma HIV-1 RNA load was 4.10 log 10 ⁡ copies/mL; median CD4 cell count was 258 cells/ μ L. At week 48, 111/135 (82%) of DRV/r OD and 109/137 (80%) of DRV/r BID patients achieved an HIV-1 RNA load <50 copies/mL. No patient developed primary PI RAMs. Conclusion . DRV/r 800/100 mg OD in combination with ≥2 optimised NRTIs led to virological suppression <50 copies/mL in 82% of NNRTI-experienced, PI-naïve patients by week 48.